Integrated Phlebotomy Training Model for Healthcare Workers in a Private Hospital in North Minahasa - Iwan W. Joseph; Tinneke E. M. Sumual; Rolles N. Palilingan; Viktory N. J. Rotty (JR Education, 2026)
Phlebotomy is a high-frequency clinical procedure whose quality strongly affects laboratory accuracy, patient safety, service efficiency, and public trust in hospital care. This article examines the governance of a phlebotomy training model for healthcare workers in a private hospital in North Minahasa by focusing on planning, implementation, evaluation, and formulation of an integrated model. The study used a qualitative descriptive approach. Data were collected through in-depth interviews, participatory observation, focus group discussion, and documentation of training plans, standard operating procedures, learning activities, and evaluation records. Data were analyzed thematically through transcription, coding, categorization, triangulation, and interpretation based on educational management and health-training theories. The findings show that training planning had been initiated through curriculum preparation, competency-need identification, standard operating procedures, and management involvement. However, planning remained more administrative than performance-based because it was not fully supported by a measurable competency map, modern simulation facilities, certified instructors, and digital learning infrastructure. Training implementation combined lectures, demonstrations, and laboratory practice, but it was still dominated by conventional methods and limited simulation. Evaluation showed improvement in knowledge, but psychomotor skill, workplace behavior, and organizational outcomes were not yet measured consistently. The proposed model integrates ADDIE, POAC, blended learning, simulation, mentoring, Kirkpatrick-based evaluation, clinical audit, and continuous professional development. The model is expected to strengthen technical competence, communication ethics, patient safety, data-based monitoring, and sustainable service quality improvement.